AB0943 Sustained improvements with up to 104 weeks of apremilast monotherapy in biologic-naÏve subjects with active psoriatic arthritis: results from a phase 3b, randomised, controlled trial. (12th June 2018) - Nash, P.; Ohson, K.; Walsh, J.; Delev, N.; Nguyen, D.; Teng, L.; Paris, M.; Gomez-Reino, J.J.; Aelion, J.A.
Abstract : Background: ACTIVE is the first apremilast (APR) study to demonstrate onset of response to APR starting at Week 2 in biologic-naïve subjects with psoriatic arthritis (PsA) who may have had exposure to 1 prior conventional disease-modifying anti-rheumatic drug. Objectives: To determine the efficacy and safety of APR through Week 104 in the ACTIVE study. Methods: Subjects were randomised (1:1) to receive APR 30 mg BID or placebo (PBO) for 24 weeks; thereafter, all subjects received active treatment with APR. The long-term durability of APR treatment on various PsA manifestations was evaluated. Along with safety data, adverse events (AEs) of diarrhoea were further characterised. Results: A total of 219 subjects were randomised (APR: n=110; PBO: n=109); 89% (142/160) of subjects entering year 2 of the study completed the Week 104 visit, and 64.8% (142/219) of randomised subjects completed the Week 104 visit, including 60.9% (67/110) of subjects randomised to APR at baseline. Early onset of response to APR was observed for ACR20 response and improvements in DAS-28 (CRP), HAQ-DI, enthesitis (in subjects with enthesitis at baseline), and morning stiffness severity. With continued APR exposure, the Week 104 ACR20 response rate was 62.9%; ACR50 and ACR70 response rates were 33.3% and 20.1%, respectively. Mean percent change in swollen joint count was −75.9%, and mean percent change in tender joint count was −68.3%. In all, 65.7% of APR subjects with baseline enthesitis reached a Gladman Enthesitis Index score of 0 (table 1). More than half of the APR subjects had improvements in morning stiffness severity. Sustained improvements in physical function were also observed, with a mean change of 5.9 in the SF-36v2 Physical Functioning score and a mean change in HAQ-DI score of −0.37 at Week 104. Safety findings for the APR-exposure period were consistent with previous reports. The most commonly reported AEs (≥5% of subjects) during the APR-exposure period were bronchitis (5.3%), headache (6.3%), hypertension (6.3%), nasopharyngitis (8.3%), upper respiratory tract infection (8.3%), nausea (8.7%), and diarrhoea (16.5%). New incidences of protocol-defined diarrhoea (≥2 watery/liquid stools/day) decreased during long-term APR exposure. Over the APR-exposure period, serious AEs occurred in 7.3% of subjects; 8.3% of subjects discontinued treatment due to an AE. No serious opportunistic infections, including tuberculosis reactivation, or cases of serious depression were seen. Week 52 and Week 104 analyses were data as observed among all subjects who received APR, regardless of when APR treatment started (baseline, Week 16 or Week 24); actual number of subjects may vary for each end point depending on availability of data. *Evaluated in subjects with enthesitis at baseline (Gladman Enthesitis Index score >0). ACR20/50/70=≥20%/≥50%/≥70% improvement in modified American College of Rheumatology response criteria; n/m=number of responders/number of subjects with sufficient data for evaluation; DAS-28=28 joint count Disease Activity Score; CRP=C reactive protein; SF-36v2=36 item Short-Form Health Survey version 2; HAQ-DI=Health Assessment Questionnaire-Disability index; MCID=minimal clinically important differences. Conclusions: In biologic-naïve subjects treated with APR, early onset of effect was observed across PsA manifestations, including morning stiffness severity and enthesitis, with sustained improvements through Week 104 in the subjects continuing APR therapy. AEs were consistent with those reported for other APR phase 3 PsA and psoriasis studies. Disclosure of Interest: P. Nash Grant/research support from: Celgene Corporation, K. Ohson Grant/research support from: Celgene Corporation, J. Walsh Grant/research support from: Amgen, Pfizer, UCB, Celgene Corporation, Novartis, N. Delev Employee of: Celgene Corporation, D. Nguyen Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, M. Paris Employee of: Celgene Corporation, J. Gomez-Reino Grant/research support from: Roche, Schering-Plough, Consultant for: BMS, Pfizer, Roche, Schering-Plough, UCB, J. Aelion Grant/research support from: AbbVie, Ardea Biosciences, AstraZeneca, BMS, Celgene Corporation, Centocor, Galapagos, Genentech, GlaxoSmithKline, Human Genome Sciences, Janssen, Eli Lilly, Merck, Mesoblast, Novartis, Novo Nordisk, Pfizer, Roche, Sanofi-Aventis, Takeda Pharmaceuticals, UCB, Vertex Pharmaceuticals